Dimethyl fumarate modulates neutrophil extracellular trap formation in a glutathione- and superoxide-dependent manner - Hoffmann, Jochen; Schäkel, Knut; Enk, Alexander; Hadaschik, Eva (British journal of dermatology, 2018)
Background Neutrophil (polymorphonuclear) granulocytes (PMN) have been shown to contribute to the pathogenesis of psoriasis by releasing interleukin-17 and LL37-DNA complexes via neutrophil extracellular traps (NETs), webs of chromatin strands decorated with antimicrobial peptides, in psoriatic skin. Fumaderm®, a fumaric acid ester (FAE) formulation consisting of different FAE salts, has been successfully used to treat psoriasis for decades. Most recently, FAE treatment was reported to inhibit NET formation in murine epidermolysis bullosa acquisita. Objectives To elucidate the effect of FAE treatment on human psoriasis and healthy donor NET formation. Results Among the compounds present in the FAE formulation, dimethyl fumarate (DMF) pretreatment of human psoriasis and healthy donor PMN resulted in a consistent inhibitory effect on NET formation in response to phorbol 12-myristate 13-acetate but not to platelet activating factor and ionomycin. This effect was l-glutathione (GSH) dependent and involved a decrease in reactive oxygen species (ROS) production, a key event in NET formation. In contrast, G-protein-coupled signalling and protein synthesis were not involved. Monomethyl fumarate (MMF) was found to slightly reduce ROS production without affecting NET formation. Conclusions We report DMF as a potent, stimulus-specific, GSH- and ROS-dependent modulator of NET formation. Our results support the notion that modulation of NET formation contributes to the beneficial effects of FAEs in a variety of inflammatory conditions.